Temas transversais e letramento nas séries iniciais do ensino fundamental: para além da transversalidade temática - Thadei, Jordana Lima de Moura (2006)
This dissertation aims at investigating the contribution of thematic projects development to the construction/widening of literacy. The thematic projects investigated were developed with students from the fourth grade by the researcher herself. They refer to two of the Transversal Themes proposed by Parâmetros Curriculares Nacionais (PCNs) Sexual Orientation and Health and they are the corpus of our research. As an investigation of the researcher practices, this research is characterized as an actionresearch. Using a descriptive-interpretative methodology, it attempts to investigating the approach of language/genre in the projects, considering, as so, the practices and events of literacy, the genre within the projects and how they were approached in reading, writing and oral events. To fulfill that, it is based, first of all, in theories of literacy considering its conceptual trajectory, its patterns, its plural and situated nature, its relations with the school and with the teacher s development and a consistent emerging of contemporary literacy. Secondly, it is based on studies referring to the culturally sensitive practices, specially the pedagogy of projects. It resumes the transversality concepts, interdisciplinarity and transdiciplinarity and it analyses these concepts considering the PCNs, attempting to establish a relation between the practices that are based on these concepts and the construction of literacy(ies). Finally, it establishes some criteria to be considered in the selection and approach to genre in the development of thematic projects and it presents ways and difficulties to be overcome in the implementation of the suggested practices